Teleconsultation integration protocol for diet clinic within dietetics professional practicum at teaching hospital - Abu Zaid, Zalina; Mat Daud, Zulfitri ‘Azuan; Badrul Hisham, Muhammad Nazirul Asri (Human Resource Management Academic Research Society, 2023)
Background/Problem: The primary goal of the clinical internship for dietetic interns is to foster their competency in effectively managing the nutrition of patients. Amid the COVID-19 pandemic, the Ministry of Higher Education mandated that students refrain from physical attendance at universities. The significance of teleconsultation in the realm of dietetic practices has become even more apparent during this period, particularly for patients referred to dietitians and for students honing their patient management skills within the diet clinic. Effective planning and adherence to teleconsultation protocols are imperative to mitigate any delays in delivering crucial medical nutrition therapy (MNT) to both existing and new clients. Consequently, there's a heightened need to underscore the competency of nutrition management skills among dietetic interns. Purpose: This study seeks to implement a teleconsultation protocol for nutrition management within a diet clinic. Design: Presented here is a streamlined protocol for conducting teleconsultations within a Diet Clinic. Conclusion: The teleconsultation protocol devised and employed in this study for the Diet Clinic serves as a pivotal instrument for administering MNT, ensuring precise nutritional management for patients, and affording dietetic interns the opportunity to refine their skills in an online setting.